(untitled) (Experimental biology, 2015)
The results of the analysis of the intensity of the main fruiting trees and shrubs in the Ile-Alatau State National Park are provided in the article. The heterogeneity of the intensity of fruiting by years and observations on individual species,especially pronounced in Celtis caucasica, Armeniaca vulgaris and Malus sieversii, Juniperus pseudosabina, J.sibirica were noted the authors. The direct relationship lean years with the features of weather conditions during flowering and fruit setting was also observed.